Repensando el requisito de legalidad en el arbitraje internacional de inversión - Alarcón Loayza, Nicolás (2020)
In this article, the author intends to look into the identity of the legality requirement in international investment arbitration. For this purpose, first, the author offers a formulation of the legality requirement. Second, he provides a legal justification of the requirement based on the elements that make it up part of it as well as the rationale of international investment law. Finally, the author points out some consequences that follow the proposed justification. The author uses relevant arbitral awards in order to contrast the justification proposed with the on-going practice of arbitral tribunals, arguing that the legality requirement is an expression of the validity requirement of the investment as an object of protection under international investment law.